RELIGIOUS INDIVIDUALISM, SPIRITUALITY AND ALTERNATIVE RELIGIOUS CONCEPTS OF GAYS AND LESBIANS IN SERBIA (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
This work presents experiences and practices of gay men and lesbians who opted for alternative religious concepts, self-spirituality or an individual concept of God. Marginalized gay men and lesbians in Serbia are forced to consciously choose between religious traditions to which they belong to by birth and for which their same sex orientations and behaviours are unacceptable, and alternative religious concepts, noninstitutional individual eclectic religious practices and beliefs they create on their own. Search for that particular expression on the spiritual market which would in the best possible way allow harmonization of sexual desires, behaviours and religious identity, the search for forms of religion and spirituality which are compatible with the gay and lesbian sexuality, goes on outside of formal institutions within vary different movements of the New Age spirituality.
Keywords: Religious individualism; alternative religious concepts; gay and lesbian identities; sexual orientation; spirituality